Pengembangan Wilayah Terkena Krisis Studi Kasus: Bekasi - Nurzaman, Siti Sutriah (Journal of Regional and City Planning, 1999)
The impact of multi-dimensional crisis did not spread evenly in all regions of Indonesia. As part of Jakarta mega-urban, Bekasi suffered greater Impact than other parts of Indonesia. Relying heavily on foreign and domestic investments, without fostering local economic forces, brought Bekasi into crash during the crisis. Development of local economic and rehabilitation of the physical environment could bring Bekasi into a better condition.